A Sustainability Assessment Framework for Agricultural Land Remediation in China. (10th July 2017) - Hou, Deyi; Ding, Zhenyu; Li, Guanghe; Wu, Longhua; Hu, Pengjie; Guo, Guanlin; Wang, Xingrun; Ma, Yan; O'Connor, David; Wang, Xianghui
Abstract: China has an extensive agricultural land degradation issue due to pollution, with 19·4% of its agricultural land being contaminated. The government has released an ambitious Soil Pollution Prevention and Remediation Action Plan, aiming to remediate millions of hectares of contaminated agricultural land within the next several years. Amongst the many challenges facing the Action Plan, there is a need to assess the sustainability of these actions, especially in arid and semi‐arid regions where rehabilitation of degraded land is particularly challenging. There is a growing body of literature addressing the sustainability of remediation at industrial sites, but the remediation of agricultural land involves different sustainability concerns and, therefore, different indicators. To help address this issue, we propose a framework, which encompasses four impact categories, 11 subcategories, and 32 indicators, to assess the sustainability of agricultural land remediation. The proposed sustainability assessment framework was applied to five cases of agricultural land remediation, and the implications to policy makers and practitioners are discussed. An in‐depth life cycle assessment was also conducted for the remediation of agricultural land in an arid region of northern China. This study suggests that agricultural land remediation projects in China need to pay more attention to social aspects of sustainability and provide further scientific evidence to prove agricultural sustainability. It is imperative to conduct scientific research and develop policy instruments to progress life cycle sustainability in agricultural land remediation. Copyright © 2017 John Wiley & Sons, Ltd.